Exploring Indonesian College Students' Levels and Factors of English Speaking Anxiety - Sebayang, Rheina Elsa br; Dangin, Dangin (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study was aimed to investigate the level of anxiety about speaking English among students in Indonesia and examines the contributing factors. Using a survey research design, this research integrates descriptive statistical analysis with additional interviews to enrich and supporting the data collected. The participants consisted of 60 fifth semester psychology students. Data collection involved the use of a Likert scale questionnaire to categorize responses. The results revealed a spectrum of speaking anxiety levels among students: the majority (53.33%) showed high levels of anxiety, 20% reported quite high levels of anxiety, 8.33% experienced moderate levels of anxiety, and 3.33% showed very low levels of anxiety. .Analysis of these findings shows a trend of high speaking anxiety among the participants. This anxiety is influenced by various factors, including lack of self-confidence, fear of being judged, grammatical inaccuracies, and an unsupportive environment. Key Words: English, Speaking anxiety